The Correlation between Students' Perception Toward Teachers' Pedagogical Competence and Their Achievement in English Subject at SMA Islam NU Pujon - Indra Rouhul Wahidah (Graduate Program, University of Islam Malang, 2021)
AbstractImproving student outcomes can be influenced by the basic role of the teacher, one of them is pedagogical competence. It is crucial because reflected in the curriculum and learning process implementation, and English teacher is a key role in effective language. The purpose of this study was to analyze the students’ perception of English teachers’ pedagogical competence, to know the students' achievement, and to determine the correlation between students’ perception toward teachers’ pedagogical competence and their achievement in English subject at SMA Islam NU Pujon. Being designed in a correlational study, the sample was 92 students at twelfth grade and used simple random sampling technique. The instrument in this study was the questionnaires and tests. The result of the responses from students regarding the questionnaire and test were in the medium category, and the result showed that the correlation coefficient value was .373 which means the relationship is positive. Furthermore, the sig. value was .000 which was less than .005 means that there was a correlation between students’ perception of English teachers’ pedagogical competence and their achievement. Therefore, the higher English teachers’ pedagogical competence, the higher the students’ English achievement Keywords: students’ perception, pedagogical competence, students achievement